Teacher Candidates’ Perceptions of School Organization: Fundamental inconsistencies between expectations and experiences - Cherubini, Lorenzo (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractPreservice teacher-candidates enrolled in teacher education programs across Canada are exposed to the nuances of school organization during their practice-teaching assignments. Although the literature is full of scholarship about the concerns of new teachers, less attention has been given to school organizational factors as sources of dissonance for new teachers and preservice teacher education candidates. This study employed quantitative and qualitative methods to determine the effect of the practicum experience on prospective teachers’ beliefs about school organization in Ontario. The fundamental finding of the study was that participants’ experiences during their teaching-practicum assignments had a significantly negative effect upon their beliefs about school organization.